PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS VII 4 SMPN 03 TELUK KUANTAN TAHUN PELAJARAN 2018/2019 - Turrahmah, Laila; Yustina, Yustina; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study was conducted in classes VII 4 SMP 03 Teluk Kuantan school year to determine the increase learning outcomes of students by implementing guided inquiry learning model. This research is a classroom action research conducted in two cycles of planning, execution and observation and reflection. The data collected in this study is the learning outcomes that emphasizes on three areas, namely knowledge, attitudes and skills. Data were collected using tests and observation sheet. The results showed learning outcomes in every sphere has increased. The cognitive value seen from the results of daily tests on the first cycle that 84,80 (B) is increased in the second cycle is 94,23 (A). Students who complete the first cycle of 19 students (73,07%) and increased in the second cycle is 26 (100%). On average of attitudes value in the first cycle, namely 70,34 (D) and increased in the second cycle 81,60 (C). Average of skills value in the first cycle, namely 70,16 (C) and increased in the second cycle is 86,40 (B). It can be concluded that the application of guided inquiry learning model can improve learning outcomes class VII 4 SMP 03 Teluk Kuantan in the academic year 2018/2019.Key Words: Model of Guided Inquiry, Learning Outcomes